From meltdown to showdown? Challenges and options for governance in the Arctic - Humrich, Christoph; Wolf, Klaus Dieter (2012)
Abstract: "For several years now climate change, the hunger for raw materials, and geostrategic interests have once again moved the allocation of sovereignty and exploitation rights in the Arctic back to the foreground. In this PRIF report the authors present in search of a promising political organizational model for the Arctic region, various scenarios for how Arctic governance might look one day. The authors favor a model of integrated multi-level governance and present measures demonstrating how this model could be implemented." (author's abstract)